The impact of fast payment technology on the liquidity management of banks : A Simulation Approach - Ikonen, Reea (My University, 2019)
The aim of this study is to analyse whether the fast payment technology has an impact on the intraday liquidity management of banks that are using Real Time Gross Settlement (RTGS) system. In order to answer the question, this study examines what is the impact of fast payment technology on the required amount of intraday liquidity, on the usage of the intraday liquidity and on the cost of liquidity. After the latest financial crisis in 2007, the understanding about the importance of liquidity management started to grow, as the Basel Committee for Banking Supervision introduced new liquidity measures for banks to better mitigate their liquidity and funding risks. For many banks these new measures were the starting point to improve their liquidity management, creating an increasing demand for knowledge on various aspects of liquidity risk. The final stage of liquidity risk takes place on the payment systems, where money flows in and out. In 2017, the payment settlement system of Euroarea, TARGET2, processed €432.8 trillion worth of payments alone. In payment systems, liquidity is a scarce resource as it comes with a cost. The cost can be either a direct fee or an opportunity cost, when the funds are used for liquidity buffers instead of profitable investments. The liquidity cost and liquidity risk create an incentive for banks and central banks to improve their intraday liquidity management. The whole banking industry is currently in a turning point as more and more services are moving online and advanced technology is required to provide the services. The need to have faster and easier ways to pay was the starting point for the development of fast payments. Fast payment systems are developed to settle payments in real time for 24 hours per day, every day of the year. For banks, implementing a fast payment system would mean that the banks need to adapt their intraday liquidity management to facilitate continuous liquidity provision. This raises a question on what kind of impact the fast payment technology has on the liquidity management of banks. Changes in payment systems are often analysed with simulator, and that is the approach also in this study. The empirical part of this study is conducted by using the BoF-PSS2 simulator, developed by Bank of Finland. Two scenarios are created based on the previous literature to facilitate the main questions of this study. In the first scenario the business hours are extended to match fast payment technology and the amount of transactions processed during the extended hours are assumed to be 30% of the normal amount of transactions. The second scenario has in addition 30% more intraday liquidity at the beginning of day. When the results of the scenarios were compared with the benchmark data, it was seen that the extension of business hours had a stabilising impact on the payment flows and it decreased the usage of intraday liquidity. Both results, together with previous literature, imply that the cost of intraday liquidity would also reduce. Based on these findings it could be concluded that the fast payment solution has positive impact on the liquidity management of banks that are using RTGS system.
Keywords: fast payments, payment systems, liquidity management, intraday liquidity, BoF-PSS2